Characterisation and treatment of spent deposited sludge of transformer oil (DSTO) by acid leaching and solvent extraction. Issue 4 (2nd October 2018) - Baba, Alafara A.; Ayodele, Joshua S.; Ameen, Oloduowo M.; Jimoh, Abdulrasaq; Johnson, Uduakobong; Jimoh, Bilikisu A.; Lawal, Amudat
ABSTRACT: The characterisation of spent transformer oil to determine its fitness for re-refining as well as the recovery of metals by hydrometallurgical treatment in chloride medium has been investigated. The leaching experiments on the spent material showed that its dissolution increases with leachant concentration performed at 75°C. Leaching studies showed that at optimal conditions, the dissolution reached 93% by 1.0 mol L −1 HCl solution within 120 min at 75°C. The solvent extraction of copper by bis(2, 2, 4-trimethylpentyl) phosphinic acid (CYANEX®272) in kerosene from a pregnant solution of aqueous spent deposited sludge of transformer oil containing 1243.4 mg L −1 Cu ++, 389.2 mg L −1 Fe ++/+++, 110.7 mg L −1 Ca ++ and 235 mg L −1 Al +++ was studied. The results for the solvent extraction give an extraction efficiency of 91.77% total copper acquired via 0.2 mol L −1 CYANEX®272 in kerosene at 27 ± 2°C within 25 min at pH 4.0. A 0.1 mol L −1 HCl solution was found to be sufficient for the stripping of about 94.77% copper from the loaded organic phase. The Fourier transform–infrared spectroscopic analysis of the loaded organic phase supports the stripping experiment as there was no Cu metal ion present in the separated organic phase.